Analyzing the Effect of Board of Commissioners’ Characteristics, Managerial Ownership, and Financial Performance on Financial Risk Disclosure - Muhammad Syafwan Hady (Sebelas Maret Business Review, 2018)
This study aims to examine the role of the board of commissioners’ characteristics, managerial ownership, and financial performance on financial risk disclosure. The target population of this study was sharia banks registered in the Indonesian banking directory in 2012-2016. This study used secondary data in the form of annual financial statements obtained from the source sites of each bank. Using purposive sampling, 11 sharia banks in Indonesia were selected as the appropriate sample. This study employed a scoring technique to measure the level of financial risk disclosure. The results show that the independent variables including the board of commissioners size, independent board of commissioners proportion, profitability, and size as the control variable significantly influenced the variable of FRD. However, the variable of CAR, FDR, and managerial ownership had no effect on financial risk disclosure. The result of F test showed that independent variables included in the regression model simultaneously affected the dependent variable.